Structural Strength of Buildings at the Islamic University of Indonesia Hospital - Indra Tri Saputra; Noor Cholis Idham; Mahadevi Effia Arkan (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
The 2006 earthquake, with a magnitude of 6.3 and an epicenter in Potrobayan Hamlet, Bantul, Yogyakarta, caused significant damage to building structures in the area. This highlights the importance of structural integrity in earthquake-prone regions of Indonesia, particularly in Bantul. This study aims to analyze the structural strength of the Rumah Sakit Universitas Islam Indonesia (RS UII) against potential earthquakes over the next 50 years. This aligns with the building lifespan guidelines set by the Minister of Public Works Regulation No. 45 of 2007, which states that buildings should be evaluated and possibly repaired after 50 years. In this study, the author utilized RESIST software to assess the structural integrity of RS UII in the face of future seismic events. The results revealed weaknesses in the building's structure, indicating that it may not withstand the displacement caused by seismic loads. Therefore, structural reinforcement is necessary to enhance the building's resistance to larger earthquakes. Based on these findings, this study provides recommendations for structural improvements to ensure the hospital's earthquake resilience for the next 50 years, thus preventing significant structural damage.